2009
DOI: 10.1590/s1679-62252009000100015
|View full text |Cite
|
Sign up to set email alerts
|

Stirring, charging, and picking: hunting tactics of potamotrygonid rays in the upper Paraná River

Abstract: Hunting tactics of potamotrygonid freshwater rays remain unreported under natural conditions. Three main foraging tactics of Potamotrygon falkneri and P. motoro are described here based on underwater observations in the upper Paraná River. Both species displayed similar behaviors. The most common tactic was to undulate the disc margins close to, or on, the bottom and thus stirring the substrate and uncovering hidden preys. Another tactic was to charge upon prey concentrated in the shallows. The least common ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 5 publications
0
23
0
1
Order By: Relevance
“…In the rio Paraná basin, there are at least six rio Paraná potamotrygonids (P. brachyura, P. castexi, P. falkneri, P. hystrix, P. motoro, and P. schuhmacheri), all of them found just downstream from Sete Quedas Falls. After the impoundment, stingrays appeared in several kinds of environments in the upper rio Paraná basin (Agostinho et al, 2004;Garrone-Neto et al, 2007;Garrone & Sazima, 2009). Fishers of the floodplain above the Itaipu Reservoir had never seen those fish before; thus, several accidents occurred during fishing, mostly when seining on sand beaches at night.…”
Section: Potamotrygonidaementioning
confidence: 99%
“…In the rio Paraná basin, there are at least six rio Paraná potamotrygonids (P. brachyura, P. castexi, P. falkneri, P. hystrix, P. motoro, and P. schuhmacheri), all of them found just downstream from Sete Quedas Falls. After the impoundment, stingrays appeared in several kinds of environments in the upper rio Paraná basin (Agostinho et al, 2004;Garrone-Neto et al, 2007;Garrone & Sazima, 2009). Fishers of the floodplain above the Itaipu Reservoir had never seen those fish before; thus, several accidents occurred during fishing, mostly when seining on sand beaches at night.…”
Section: Potamotrygonidaementioning
confidence: 99%
“…Potamotrygonids are carnivorous and prey on a variety of animals Moro et al, 2012;Shibuya et al, 2012). Their hunting tactics include some with high metabolic costs, e.g., undulating their disc margins to disturb the substrate and uncover hidden prey or charging prey concentrated in shallow water (Garrone-Neto & Sazima, 2009a;Garrone-Neto & Sazima, 2009b;Garrone-Neto & Uieda, 2012). Thus, it is possible to summarise the activity patterns of potamotrygonids in accordance with Gray's scale (Gray, 1954), which includes active, intermediate, and sluggish activity levels.…”
Section: Introductionmentioning
confidence: 99%
“…Information on the locomotory modes of Neotropical freshwater stingrays (Potamotrygonidae) is available only for a few species and is insufficient. GARRONE- NETO & SAZIMA (2009) observed that Potamotrygon motoro (Müller & Henle, 1841) and P. falkneri Castex & Maciel, 1963 in the field undulate their pectoral fins in the bottom to uncover buried prey. However they do not mention the movement of the pelvic fins, which may be employed during foraging to decrease disturbance of the benthos, thus allowing for prey detection by the lateral line canals (ROSENBERGER 2001, SHIBUYA et al 2010, 2012.…”
mentioning
confidence: 99%